Implementation of Participatory Learning as a Realization of Process Standards in the Assurance and Quality Control of Community Education at PKBM Garuda Giver - Firlin Ramadisha; Rahmat Fahmi (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
This article examines the implementation of participatory learning as a manifestation of process standards in quality assurance and quality control of community education at PKBM Garuda Giver, Pekanbaru, Riau. This study uses a primary data collection through interviews with the Head of PKBM Garuda Giver. The findings indicate that PKBM Garuda Giver conducts Paket A, B, and C programs with an approach that consistently applies participatory learning principles. Paket A is conducted face-to-face with high learner involvement in every communal activity, while Paket B and C are held online while maintaining equally active participation. The curriculum development at this PKBM consistently departs from learners' real needs and problems, ensuring program relevance while strengthening the quality assurance and control cycle that grows organically from within the learning community..